THE EFFECT OF LEARNING HABITS AND LEARNING DISCIPLINE ON THE RESULT OF ACCOUNTING PRACTICE OF TRADE SERVICES COMPANY STUDENTS IN THE XI ACCOUNTING CLASS IN 48 AND 50 STATE VOCATIONAL HIGH SCHOOL JAKARTA - Yuliwarni, Eka; Susanti, Santi; Zulaihati, Sri (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
The purpose of this study is to find out whether study habits and study discipline affect the learning outcomes of students' accounting practicum trading services at SMK Negeri 48 and 50 Jakarta. The population in this study were students of class XI Accounting at 48 and 50 State Vocational School High School, totaling 150 students. Data were collected through the distribution of questionnaries. The data analysis technique used is descriptive statistical analysis, analysis requirements test, multiple regression analysis (t test and F test), multiple correlation coefficient test, and determination coefficient test using SPSS software. The results of the analysis of study habits data show the results of t count of 1,996 > t table of 1,982, which means study habits have a partial effect on learning outcomes. The same results were also obtained from learning discipline with t count 3,271 > t table 1,982, this means that learning discipline has partial effect on learning outcomes. Simultaneously there is an influence between study habits and learning discipline on learning outcomes. This can be seen from the calculated F value of 7.444 > F table 3.08. There is a positive relationship between study habits and learning discipline on learning outcomes and correlated with a multiple correlation coefficient score of 0.240, so the hypothesis is accepted. Then the coefficient of determination (R2) shows a result of 7.3% where this result is the percentage of the influence between study habits and learning discipline on learning outcomes, while the rest is the influence of other variables not included in this study.